I contorni di una relazione speciale: L’Alleanza turchia-Azerbaijan dalla Rivoluzione del 1917 Alla Guerra del Karabakh del 2020 - GÖKSEL, OĞUZHAN (My University, 2022)
This article argues that the multi-dimensional cooperation between Turkey and Azerbaijan constitutes a \"special relationship\" - the likes of which can be found in cases such as the durable US-UK alliance. I argue that neo-realist, neo-liberal and purely pragmatist political economic viewpoints are insufficient to grasp the \"emotional and ideational essence\" of Turkey-Azerbaijan alliance which is rooted in the continuing influence of Pan-Turkism on their national identities. Hence, I propose that the English School and the Social Constructivist approach could better explain Turkey-Azerbaijan ties as both underline the importance of ideational and non-materialistic elements in foreign policy behavior. To test our hypothesis, the article studies in detail the main contours of Turkey-Azerbaijan relations over the last century and locate the meaning of the alliance within the broader goals of Turkish and Azerbaijani foreign policies. Two specific periods are used as in-depth case studies, namely the notable issue of the \"Sibling’s Aid\" (1918-1922) and the recent 2020 Second Karabakh War. It will be argued that in both of these momentous periods, the peoples and governments of the two sides provided essential support to each other without necessarily expecting short-term pragmatic returns. In its penultimate section, the article also briefly covers the past and present of Turkey-Armenia relations and discuss the influence of Armenia on the making of Turkish foreign policy towards the Caucasus.
Keywords: Sosyal ve Beşeri Bilimler; Siyaset Bilimi; Uluslararası İlişkiler; Siyasi Tarih; Uyuşmazlık Analizi ve Çözümü; Social Sciences and Humanities; Political Science; International Relations; Political/Diplamatic History; Conflict Analysis and Resolution; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; ULUSLARARASI İLİŞKİLER; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; INTERNATIONAL RELATIONS; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; Social Sciences & Humanities